Muslim Youth: Prejudice and Responses in Saadia Faruqi’s Yusuf Azeem is not a Hero - Teguh, Ayudya Salsabila; Zakky, Akhmad; Oktafiyani, Elve (Muslim English Literature, 2024)
This research aims to investigate the prejudice experienced by young Muslims in the United States and examine their responses as portrayed in Saadia Faruqi’s Yusuf Azeem is not a Hero (2021). The writers use close textual analysis in analyzing the primary text to examine the prejudice and responses portrayed by the young Muslims in the novel. In doing so, the writers employ Gordon Allport's theory of prejudice to comprehend the prejudice experienced by young Muslims and Simpson & Yinger's theory of response to prejudice to examine the responses of young Muslims. The results of the analysis reveal that young Muslim-Americans experience prejudice in various forms, which affects their social lives and shapes their identities. Their responses to this prejudice also vary, depending on the specific situation, their personal experiences, and their understanding of the 9/11 tragedy. Thus, responses were seen in the form of resistance and negotiation of their identities. This study reveals that the 9/11 tragedy significantly impacted the Muslim community, especially Muslim youth who did not experience the tragedy but being subjected to discrimination and physical violence.